Implementasi Metode Trend Projection pada Sistem Prediksi Penggunaan Consumable Berbasis Web - Dwi Ismiyana Putri; Putri Nikmaturidha; Yogi Kristiyanto; Solikin; Muhamad Baydhowi; Sumardiono (Ikatan Ahli Informatika Indonesia, 2024)
Recording the use of consumables in the quality department has not been done consistently and is still done by recording on a piece of paper collection form, then transferring to an excel form, causing errors such as lack of consumable stock before the time the purchase should be made. This causes excess funds and the use of other funds to buy the shortage of consumables needed. This research uses the Extreme Programming (XP) system development model with the Trend Projection method, aiming to overcome existing problems by predicting consumable forecasts based on trends from previous item data. The output of the Trend Projection Method forecasting can help, simplify, and speed up the admin in determining what items are worth buying for use in the next month with a more detailed amount.